2008
DOI: 10.1631/jzus.b0820051
|View full text |Cite
|
Sign up to set email alerts
|

Advanced primary peritoneal carcinoma: clinicopathological and prognostic factor analyses

Abstract: Abstract:Objective: To investigate the factors favoring a positive prognosis for advanced primary peritoneal carcinoma (PPC). Methods: Twenty-four cases meeting the criteria for PPC were analyzed retrospectively for the clinicopathologic profiles. Immunohistochemistry was used to determine the expressions of p53, Top2α, Ki-67 and Her-2/neu. Then all these clinicopathological factors and molecular markers were correlated with the prognosis. Results: There were 15 cases of primary peritoneal serous papillary car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
1
9
0
1
Order By: Relevance
“…PPC is generally observed in advanced-age and post-menopausal women. Although affected patients in different age groups have been reported, the typical age of patients with PPC ranges from 57 to 66 years, with 75-88.7% of patients reported to be postmenopausal women [3,11,12]. Our patient group demonstrates similarities with other studies with regard to the mean age of the patients (63 years) and their menopausal status (91.0% postmenopausal).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…PPC is generally observed in advanced-age and post-menopausal women. Although affected patients in different age groups have been reported, the typical age of patients with PPC ranges from 57 to 66 years, with 75-88.7% of patients reported to be postmenopausal women [3,11,12]. Our patient group demonstrates similarities with other studies with regard to the mean age of the patients (63 years) and their menopausal status (91.0% postmenopausal).…”
Section: Discussionsupporting
confidence: 72%
“…In 3 separate evaluations of patients who had been treated with platinum and alkylating agents before taxane therapy, median survival times were 24, 19 and 15 months, respectively [13,14,15]. In contrast, studies on prognosis after taxane therapy reported longer survival times, and the median survival times were 33, 41 and 42 months, respectively in 3 separate studies [3,11,12]. All patients included in our retrospective analysis received taxane therapy which conceivably had an impact on our patients' longer median survival time (31 months).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fakat primer peritoneal kanserlerin gerek overleri hiç tutmaması veya minimal tutması gerekse de hastalığın davranış şekli-nin özellikle üst batını da tutacak şekilde difüz mikronodüler yayılması nedeni ile sitoredüktif cerrahinin over kanserli hastalarda olduğu gibi yeterli olamayabileceği vurgulanmaktadır. [35][36][37] Fakat diğer kapsamlı çalışmalarda, primer peritoneal kanserlerde de yeterince "debulking" yapılabildiği ve optimal "debulking" yapmanın hasta sağkalımına belirgin avantajlar sağladığı belirtilmektedir. [38][39][40] Bu hastalarda optimal "debulking" %70'in üzerinde olup, over kanserleriyle benzerlik göstermektedir.…”
Section: Kli̇ni̇k Seyi̇runclassified
“…Conversely, a positive test result in women who have (subclinical) PPC, PWC may lead to earlier diagnosis and possibly improve the prognosis. Studies on PPC have shown that the median survival is 23.5 (95 % CI, 18.6–39.8) [ 14 ] to 42 (95 % CI 22–62) months [ 15 ], but the advantage in survival for early diagnosis of PPC is not known.…”
Section: Introductionmentioning
confidence: 99%